Students and teachers’ perceptions of gamification in English language learning and teaching - Pangaribuan, Darman; Kenny, Kenny; Tanadi, Vincent; Sidabutar, Gilbert; Sibuea, Rebecha R; Rambe, Kartina Rahmadhani (Universitas Mulawarman, 2026)
This paper explores students’ and teachers’ perceptions of gamification in English language learning and teaching at SMA Negeri 1 Sunggal, Indonesia. Using a descriptive qualitative method, data were collected from 72 students and 2 English teachers through questionnaires, interviews, and classroom observations. Findings showed that both students and teachers perceived gamification positively, recognizing its capacity to increase motivation, engagement, and learning effectiveness, particularly in grammar and vocabulary. Gamified tools such as Quizizz made lessons more interactive, enjoyable, and student-centered. However, challenges such as limited internet connectivity, time constraints, and teachers’ digital competence hindered effective implementation. The study concludes that gamification is most effective when supported by sufficient infrastructure, professional training, and balanced instructional design.